Risking change : experimenting with local forest management committees in Jamaica - Geoghegan, Tighe (International Institute for Environment and Development LondonGB, 2003)
Presents the results of research by the Caribbean Natural Resources Institute and the Jamaica Forestry Department with regard to the establishment of two Local Forest Management Committees to involve stakeholders in managing forest reserves.